Synthesis and Characterization of Two New Schiff Base Ligands and their Complexes with some Transition Metals - Yazici, Aysegul; Aydin, Huseyin; Canpolat, Erdal; Kaya, Mehmet (Chem Soc Pakistan, 2013)
Two Schiff base ligands, 4-{(E)-[(5-phenyl-6H-1,3,4-thiadiazine-2-yl) imino] methyl} benzene-1,3-diol ((LH)-H-1) and 4-bromo-2-{(E)-[(5-phenyl-6H-1,3,4-thiadiazine-2-yl) imino] methyl} phenol ((LH)-H-2) have been prepared from 5-phenyl-6H-1,3,4-thiadiazine-2-amin (A), 2,4-dihydroxy benzaldehyde (1) and 5-bromo salicylaldehyde (2). With this ligands, complexes were synthesized using Ni(II), Co(II) and Cu(II) salts with a metal: ligand ratio of 1:2. It was determined that the bidentate behavior of the ligand is accomplished via the phenolic oxygen and the azomethine nitrogen atoms. The structures of the ligands and their complexes are proposed based on elemental analysis, magnetic moments, thermogravimetric analyses (TGA) and spectroscopic (IR, UV-Vis and H-1-NMR) data.
Keywords: Schiff base; transition metal complexes